Nota de l’Editora - Melinda Dooly (Universitat Autònoma de Barcelona, 2014)
This issue starts off our fourth year of publishing this journal. For 2014, we maintain the traditions that have worked well for us thus far -the different sections that include one invited guest author, an interview of an expert related to our field, a book review and of course, articles by the exceptionally talented students and young researchers working in the area of teaching and learning language and literature. (...)